Effects of surface modification and thermal annealing on the interfacial dynamics in core–shell nanocomposites based on silica and adsorbed PDMS. (September 2015) - Klonos, Panagiotis; Kyritsis, Apostolos; Pissis, Polycarpos
Graphical abstract: Highlights: Interfacial polymer fraction and dynamics are suppressed on modified silica (smoothened surfaces). Surface modification of silica decreases the contact points with the polymer. Particles surface and polymer topology dominate on interfacial dynamics. Interfacial characteristics can be well described in terms of bimodal conformations. Abstract: Core–shell structured nanocomposites of polydimethylsiloxane (PDMS) adsorbed onto high specific surface area (342 m 2 /g) fumed silica nanoparticles (initially ∼8 nm in size) were studied employing differential scanning calorimetry (DSC) and broadband dielectric spectroscopy (BDS). PDMS was adsorbed mainly onto the surfaces and voids of silica aggregates (∼300 nm). Nanozirconia grafting on initial silica resulted in smoothening of external surfaces and in weaker polymer adsorption. The latter could be monitored by BDS via recording directly the relaxation mechanism ( αint ) of polymer at the silica–PDMS interface. Surface modification led to suppression of interfacial dynamics (slower and weaker αint ). Spatial constraints (e.g. in voids and between crystal regions) were found to dominate mobility not close to the interfaces. In addition, thermal annealing of samples of enhanced interfacial mobility (unmodified surfaces) resulted in the suppression of αint, similarly to the results of surface modification. In agreement to previous findings on similar systems, the characteristics of interfacial dynamics could be interpreted in terms of density of polymer–silica contact points at the interfaces (reduced for modified surfaces), in combination with models which involve bimodal conformations of polymer chains (loop- and tail-like) adsorbed on solid surfaces.